2004
DOI: 10.1074/jbc.m407898200
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Analysis of Signal Peptide Peptidase and Homologous Human Aspartic Proteases Reveals Opposite Topology of Catalytic Domains Compared with Presenilins

Abstract: The human genome encodes seven intramembranecleaving GXGD aspartic proteases. These are the two presenilins that activate signaling molecules and are implicated in Alzheimer's disease, signal peptide peptidase (SPP), required for immune surveillance, and four SPP-like candidate proteases (SPPLs), of unknown function. Here we describe a comparative analysis of the topologies of SPP and its human homologues, SPPL2a, -2b, -2c, and -3. We demonstrate that their N-terminal extensions are located in the extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 46 publications
8
125
1
Order By: Relevance
“…35 In contrast to presenilin, SPPL proteases catalyze the intramembrane proteolysis of type II anchored membrane proteins. 17 Our inhibitor and siRNA knockdown experiments demonstrated that intramembrane cleavage of the FasL remnant APL leads to the liberation of the 11-kDa SPA fragment, which consists of the FasL ICD. FasL processing by SPPL2a is further supported by co-immunoprecipitation experiments, which demonstrate a direct interaction between both molecules (data not shown).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…35 In contrast to presenilin, SPPL proteases catalyze the intramembrane proteolysis of type II anchored membrane proteins. 17 Our inhibitor and siRNA knockdown experiments demonstrated that intramembrane cleavage of the FasL remnant APL leads to the liberation of the 11-kDa SPA fragment, which consists of the FasL ICD. FasL processing by SPPL2a is further supported by co-immunoprecipitation experiments, which demonstrate a direct interaction between both molecules (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…26 Recently, a new group of proteases that belong to the signal peptide peptidase-like (SPPL) family of intramembrane-cleaving proteases (I-CliPs) has been described. 17 They display no particular sequence homology to PS, but all contain the same active-site motifs, YD and GxGD. The crucial difference, however, is the orientation of their catalytic domain, which suggests their propensity for type II transmembrane protein substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SS-like peptides, liberated from dormant, membrane-bound precursor proteins by the activities of intramembrane-cleaving proteases such as SS peptidase, are thought to play downstream functions in cell signaling and regulation, immune surveillance, and intercellular communication. 11 An antimicrobial peptide derivative of flesh fruit fly hemolymph mimics secretory SS and inhibited SPase in the export pathway. 12 In addition to the core hydrophobic region, the functionality of SS is critically determined by juxtaposition of the charge to the cleavage bond.…”
Section: Introductionmentioning
confidence: 99%